Public charging infrastructure for plug-in electric vehicles: What is it worth?. (January 2020) - Greene, David L.; Kontou, Eleftheria; Borlaug, Brennan; Brooker, Aaron; Muratori, Matteo
Highlights: Public charging has value to users and can support PEV adoption. For PHEV, public charging displaces gasoline use. For BEV, public charging enables additional driving. Estimate functions of willingness to pay for public charging infrastructure. Existing charging infrastructure in CA is worth thousands of dollars per user. Abstract: Lack of charging infrastructure is an important barrier to the growth of the plug-in electric vehicle (PEV) market. Public charging infrastructure has tangible and intangible value, such as reducing range anxiety or building confidence in the future of the PEV market. Quantifying the value of public charging infrastructure can inform analysis of investment decisions and can help predict the impact of charging infrastructure on future PEV sales. Estimates of willingness to pay (WTP) based on stated preference surveys are limited by consumers' lack of familiarity with PEVs. As an alternative, we focus on quantifying the tangible value of public PEV chargers in terms of their ability to displace gasoline use for PHEVs and to enable additional electric (e−) vehicle miles for BEVs, thereby mitigating the limitations of shorter range and longer recharging time. Simulation studies provide data that can be used to quantify e-miles enabled by public chargers and the value of additional e-miles can be inferred from econometric estimates of WTP for increased vehicle range. Functions are synthesized that estimate the WTP for public charging infrastructure by plug-in hybrid and battery electric vehicles, conditional on vehicle range, annual vehicle travel, pre-existing charging infrastructure, energy prices, vehicle efficiency, and household income. A case study based on California's public charging network in 2017 indicates that, to the purchaser of a new BEV with a 100-mile range and home recharging, existing public fast chargers are worth about 1500 for intraregional travel, and fast chargers along intercity routes are valued at over 6500.